The springboard: Multiple modes in one spring-loaded control - Hinckley, Ken; Guimbretiere, Francois; Baudisch, Patrick; Sarin, Raman; Agrawala, Maneesh; Cutrell, Ed (CHI '06: Proceedings of the SIGCHI conference on Human Factors in computing systems, 2006)
Modes allow a few inputs to invoke many operations, yet if a user misclassifies or forgets the state of a system, modes can result in errors. Spring-loaded modes (quasimodes) maintain a mode while the user holds a control such as a button or key. The Springboard is an interaction technique for tablet computers that extends quasimodes to encompass multiple tool modes in a single spring-loaded control. The Springboard allows the user to continue holding down a nonpreferred-hand command button after selecting a tool from a menu as a way to repeatedly apply the same tool. We find the Springboard improves performance for both a local marking menu and for a non-local marking menu (“lagoon”) at the lower left corner of the screen. Despite the round-trip costs incurred to move the pen to a tool lagoon, a keystroke-level analysis of the true cost of each technique reveals the local marking menu is not significantly faster.